Horizontal Biofilter System in Tapioca Starch Wastewater Treatment: The Influence of Filter Media on the Effluent Quality - Nur Hidayat; Sri Suhartini; Dian Indriana (APTA and DTIP FTP UGM, 2012)
The aim of this research was to analyse the use of different filter media at laboratory scale under a horizontal biofilter system treating tapioca starch wastewater (TSW) to improve the effluent quality that met the national standard. The completely randomized design was used in this study. A horizontal biofilter system was designed and filled with filter media, include sand, gravel, soil (entisol type), coconut fibre and bamboo plait, in each unit. Prior feeding to the biofilter unit, TSW was inoculated with Bacillus sp. N-09. The TSW flow rate was maintained at 6 l d-1 and operated for 1-month period. The results showed that the use of sand as filter media gave a better performance in improving the TSW effluent quality followed by gravel, coconut fibre, soil and bamboo plait. The horizontal biofilter system packed with sand filter media removed 98.53 % BOD, 98.71 % COD, 88.96 % TSS, and increased pH to 8.0.